2016
DOI: 10.1038/srep27124
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Brg1 causes abnormal hair cell planer polarity, hair cell anchorage, and scar formation in mouse cochlea

Abstract: Hair cells (HCs) are mechanosensors that play crucial roles in perceiving sound, acceleration, and fluid motion. The precise architecture of the auditory epithelium and its repair after HC loss is indispensable to the function of organ of Corti (OC). In this study, we showed that Brg1 was highly expressed in auditory HCs. Specific deletion of Brg1 in postnatal HCs resulted in rapid HC degeneration and profound deafness in mice. Further experiments showed that cell-intrinsic polarity of HCs was abolished, docki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…SIM imaging demonstrated that F-actin rings and fan-shaped meshwork appeared in OHCs from the first week after birth and remained to the mature stage. Functionally, the structures of F-actin in the cuticular plate of the hearing impaired Atoh1-Brg1 − / − mice 11 with OHC morphology disrupted (Supplementary Fig. S7a) showed that, as expected, their rings were severely disrupted in the OHCs, and characteristic fan-shaped meshwork of F-actin had entirely disappeared (Supplementary Fig.…”
supporting
confidence: 52%
“…SIM imaging demonstrated that F-actin rings and fan-shaped meshwork appeared in OHCs from the first week after birth and remained to the mature stage. Functionally, the structures of F-actin in the cuticular plate of the hearing impaired Atoh1-Brg1 − / − mice 11 with OHC morphology disrupted (Supplementary Fig. S7a) showed that, as expected, their rings were severely disrupted in the OHCs, and characteristic fan-shaped meshwork of F-actin had entirely disappeared (Supplementary Fig.…”
supporting
confidence: 52%
“…Extant accounts of rapid hair cell death after exposure to noise (Oesterle, 2013) and ototoxins (Anttonen et al, 2012, 2014; Astbury and Read, 1982; Forge, 1985; Leonova and Raphael, 1997; McDowell et al, 1989; Raphael and Altschuler, 1991; Taylor et al, 2008) in guinea pig, rat, and mouse favor a general principle where scar formation coincides with hair cell elimination from the reticular lamina, and holes are prevented. Prior to the current study, exceptions have been limited to knockout mouse models (Cohen-Salmon et al, 2002; Jin et al, 2016) and focal hair cell loss in chinchillas for relatively low-level noise exposures reported by Bohne and colleagues (Harding and Bohne, 2004). The present findings indicate that acute reticular lamina breach could be a common feature of young adult cochlea, which had not been closely examined within this framework.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these models (claudin-9 and -14) show both reduced electrical resistance of tight junctions and hair cell loss, despite a normal EP. In mice, hair cell death that causes holes and EP reduction remains the exception to the rule, having only been reported in knockout models (Cohen-Salmon et al, 2002; Jin et al, 2016). On balance, observations of hair cell death from noise, ototoxins, or genetic causes support the predominance of mechanisms for quickly sealing off the reticular lamina so that electrical impedance and ionic integrity are maintained.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, progressive delocalization of GNAI-GPSM2 and aPKC at the HC apical membrane was previously reported in mutant HCs lacking the SMARCA4/BRG1 subunit of the SWI/SNF chromatin remodeling complex [54]. Loss of SMARCA4 protein between P1-P4 caused HCs to start dying from P8 however, questioning whether loss of protein polarization at the HC apical membrane might possibly be a side effect of cellular decline.…”
Section: Discussionmentioning
confidence: 93%